2018
DOI: 10.1080/15384047.2018.1529108
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibited colitis and colitis-associated cancer (CAC) through protecting mitochondrial structures of colorectal epithelial cells in mice

Abstract: Although a mountain of papers have showed that metformin plays a role in inhibiting cancers, but the mechanism underpinning this has not yet fully elucidated. Herein, we used AOM/DSS model, the clinicopathological features are similar to those found in humans, to investigate the effects of metformin as well as combination with 5-FU in the prevention of colitis and colitis associated cancer (CAC). Oral metformin significantly inhibited DSS-induced ulcerative colitis and AOM/DSS-induced CAC. Metformin also ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…On the contrary, metformin administration was effective in reducing number of tumors, the composition of resident inflammatory cells and other inflammatory scores, and the incidence of adenocarcinomas in the colon of AOM + DSS treated mice after 16-weeks. Similarly, the chemopreventive effect of metformin has been previously demonstrated [22] and the effects of IGFBP3 knockout and metformin were observed in a murine model of ulcerative colitis, showing significantly reduced colitis [30].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…On the contrary, metformin administration was effective in reducing number of tumors, the composition of resident inflammatory cells and other inflammatory scores, and the incidence of adenocarcinomas in the colon of AOM + DSS treated mice after 16-weeks. Similarly, the chemopreventive effect of metformin has been previously demonstrated [22] and the effects of IGFBP3 knockout and metformin were observed in a murine model of ulcerative colitis, showing significantly reduced colitis [30].…”
Section: Discussionmentioning
confidence: 83%
“…As IGF-binding proteins (IGFBPs) modulate the amount of bioavailable IGFs in a positive or negative manner [21,22], both the positive rate and expression grade of IGFBPs are shown in the lower panel of Figure 3. In the Normal group, the positive rates of IGF2BP1 and IGFBP2 expression in colonic samples were significantly lower (33 and 40%, respectively), whereas IGFBP3 expression was significantly higher (by 43%, p < 0.05) than that of the AOM + DSS control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 142 Additionally, numerous studies suggest the mechanism by which the diabetic drug metformin inhibits cancer cells might correlate with its mitochondrial-targeting activity to inhibit the ETC. 143 Population studies such as that of Seo et al have shown that diabetic patients treated with metformin, which inhibits ETC Complex I, present an approximately 30% reduced overall cancer incidence and mortality rate. 144 Therefore, mitochondrial-targeted therapeutics are emerging as an exciting opportunity for cancer therapy.…”
Section: Mitochondrial Targeting By Potential Therapeuticsmentioning
confidence: 99%
“…(50) In a study, metformin prevented inflamed colorectal epithelial cells and cancer cells by activating the LKB1/AMPK pathway. (51) On the other hand, metformin can inhibits the mTOR pathway in an AMPKindependent pathway by inactivating Rag GTPases. (52)…”
Section: Ampk Pathwaymentioning
confidence: 99%